An evaluation of alertness training for older adults - Milewski-Lopez, Agnieszka; Greco, Eleonora; van den Berg, Flip; McAvinue, Laura P.; McGuire, Sarah; Robertson, Ian H. (Frontiers in Aging Neuroscience, 2014)
We present an evaluation of a self-administered, biofeedback-aided, alertness training programme called the Alertness: Training for Focused Living (ATFL) Programme, which was developed as part of the Technology Research for Independent Living (TRIL) collaboration. We conducted two studies in order to evaluate the programme. A randomised controlled trial was, first of all, conducted with 40 older adults aged between 60 and 83. A series of five single case studies was then conducted to examine the suitability of the programme for use with people with more severe memory difficulties. In the randomised controlled trial, participants were assigned to the ATFL Programme or to a placebo programme. Aspects of participants’ memory, attention and executive functioning were assessed via telephone prior to and following completion of the training programmes and at 1-month, 3-month and 6-month follow-up sessions. Significant improvements in sustained attention and verbal fluency were noted in the ATFL group. The series of single case studies illustrated the importance of tailoring a programme to the needs and abilities of the clients in question. The potential benefits of the ATFL programme in terms of periodically boosting alertness and aiding executive functioning are discussed.